Anti-semitism and its metaphysical origins - Patterson, David, 1948- (Cambridge University Press, 2015)
"This book articulates a deeper understanding of the phenomenon of Jew hatred as a metaphysical aspect of the human soul. Proceeding from the Jewish thinking that the anti-Semites oppose, David Patterson argues that anti-Semitism arises from the most ancient of temptations, the temptation to be as God, and thus to flee from an absolute accountability to and for the other human being"-- Provided by publisher
Keywords: Antisemitism.; Antisemitism -- History.; Antisémitisme.; Antisémitisme -- Histoire.; antisemitism.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Antisemitism; Antisemitismus; Metaphysik; Philosophische Anthropologie; History